AKTIVITAS SISWA DALAM PEMBELAJARAN IPA KONSEP EKOSISTEM MELALUI PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING DI SEKOLAH MENENGAH - Wati, Zuraida Usdek (Universitas Islam Balitar, 2018)
The learning of Science, especially ecosystem material needs to be followed up in improving the learning, so that the students are expected to participate actively in learning and teaching process. This is also useful in improving the result of Biology learning in ecosystem material. To solve the difficulties of learning, one of considerations is improving the student ’s ability in learning process and to find the answers. One way that can be taken is to use guided inquiry learning during teaching learning takes place. Or students aredirectly involved in asking questions, searching information and conducting aninvestigation. This research is aimed at improving students ’ activity of garde VII-“C SMPN 25 Banjarmasin usingguided inquiry learning on Ecosystem material. This study is a Classroom Action Research (CAR) which is designed in two learning cycles, with each cycle consisting of 2 meetings. The subjects of this study were all students of class VII -“ C of SMP 25 Banjarmasin in academic year2014/2015. Data collection techniques used including the provision of tests, observations and questionnaires. The data obtained were analyzed qualitatively and quantitatively. The results of the study show that students ’ activity can be improved by using guided inquiry learning.